2015
DOI: 10.5120/21561-4594
|View full text |Cite
|
Sign up to set email alerts
|

3-D Air Flow in a Toroidal Natural Convection Loop

Abstract: Heat transfer characteristics of air flows in concentric toroidal annular tubes filled with porous media were numerically investigated. The toroidal annulus is constant walls temperature where the outer wall temperature is lower than the inlet temperature. The numerical methodology was based on the finite difference approximation method. The computations were performed for vertical and horizontal toroidal ring, four toroidal length and four radius ratios cases for a modified Rayleigh number range (10 ≤ Ra ≤ 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Common parameter estimation methods include the GM method, MM method, PD method, and MLE method [21][22][23], etc. H.Saleh [24] compared 5 methods for solving the parameters of the Weibull distribution using wind speed data measured in Zafarana of the Suez Gulf, Egypt, namely, average wind speed method, MLE, modified maximum likelihood method, GM method and PD method. Through RMSE analysis, the average wind speed was finally calculated, and it was found that the MLE was the best method for fitting the wind speed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Common parameter estimation methods include the GM method, MM method, PD method, and MLE method [21][22][23], etc. H.Saleh [24] compared 5 methods for solving the parameters of the Weibull distribution using wind speed data measured in Zafarana of the Suez Gulf, Egypt, namely, average wind speed method, MLE, modified maximum likelihood method, GM method and PD method. Through RMSE analysis, the average wind speed was finally calculated, and it was found that the MLE was the best method for fitting the wind speed in this area.…”
Section: Introductionmentioning
confidence: 99%